Smoke spread velocity along a corridor induced by an adjacent compartment fire with outdoor wind. (25th January 2017) - Li, S.C.; Huang, D.F.; Meng, N.; Chen, L.F.; Hu, L.H.
Highlights: Smoke velocity along corridor generated from adjacent fire room with outdoor wind. A theoretical model of smoke velocity in the corridor with outdoor wind established. Experiments were performed to investigate the velocity of smoke in the corridor. Abstract: Outdoor wind is one of the important driving forces of fire smoke movement in high-rise buildings. This paper investigates the smoke spread velocity along a corridor induced by an adjacent compartment fire with outdoor wind. Based on momentum and mass conservation laws, a theoretical model predicting the smoke spread velocity was developed. Reduced-scale experiments were performed for model validation. Correlations for smoke spread velocity in the corridor under the effect of outdoor wind were proposed. It is found that the initial velocity can be very well predicted according to the stratification stability of smoke with the criterion of Fr . Moreover, the velocity profiles along the corridor decay exponentially.